ПРОГРАМИ ПОЛІТИЧНИХ ПАРТІЙ ПРО РОБІТНИЧЕ ПИТАННЯ ТА ЕКОНОМІЧНІ РЕФОРМИ (початок ХХ століття) (Zaporizhzhia Historical Review, 2021)
One of the most burning problems of political life in Russian Empire in XIX – XX was so-called wiorker’s problem. The programmes of the liberal parties paid much attention to this problem and contaminated capitalist and socialist elements. The liberals prefer the evolutionary tactics in their vision of this problem.